Utilization of phosphogypsum in phenol removal from coking wastewater - Dmytro Yelatontsev (Journal of Hazardous Materials Letters, 2023)
The paper presents the results of the application of raw phosphogypsum as an adsorbent for the preliminary treatment of coke-chemical wastewater with an initial concentration of phenol 395 mg/L. Studies in batch mode have proved that phenol removal is promoted by increasing the adsorbent dose and effluent temperature, the optimal phosphogypsum dose was found to be 5 g/L. The adsorption kinetics follows a pseudo-first-order model, the maximum adsorption capacity of phosphogypsum reaches 85 mg/g, which provides purification from phenol at the level of 85–90%. The process is spontaneous and endothermic. In column mode, at an effluent flow rate of 3 mL/min and the height of the fixed bed of 15 mm adsorbent dynamic capacity reached 124 mg/g. The obtained data indicate that raw phosphogypsum, available in huge quantities in the dumps of phosphoric acid plants, can be effectively used for the pretreatment of phenolic wastewater before biological treatment.